Pattern recognition and machine learning - Anzai, Yūichirō 1946- (Academic Press, 1992)
This is the first text to provide a unified and self-contained introduction to visual pattern recognition and machine learning. It is useful as a general introduction to artifical intelligence and knowledge engineering, and no previous knowledge of pattern recognition or machine learning is necessary. Basic for various pattern recognition and machine learning methods. Translated from Japanese, the book also features chapter exercises, keywords, and summaries.
Includes bibliographical references (pages 387-402) and index. - Print version record
Keywords: Pattern perception; Machine learning; Perception des structures; Apprentissage automatique; COMPUTERS; Computer Vision & Pattern Recognition; RECONHECIMENTO DE PADRÕES; APRENDIZADO COMPUTACIONAL; Reconnaissance des formes (informatique)